RISK FACTORS FOR PNEUMONIA IN ELDERLY INDONESIAN HAJJ PILGRIMS (DATA ANALYSIS OF SISKOHATKES 2023): Faktor Risiko Pneumonia Pada Jemaah Haji Indonesia Usia Lanjut (Analisis Data Siskohatkes 2023) - Fitrianti, Alvina Diva; Simanjorang, Chandrayani; Karima, Ulya Qoulan; Nurcandra, Fajaria (Jurnal Berkala Epidemiologi, 2025)
Background: Pneumonia is the most common health problem encountered during the Hajj pilgrimage and has been recognized globally as a major cause of morbidity, hospitalization and death. During the 2023 Hajj season, pneumonia is known to be among the top five diseases that cause hospitalization of elderly Indonesian Hajj pilgrims. Purpose: This research aimed to determine the risk factors for pneumonia in elderly Indonesian Hajj pilgrims. Methods: This research uses a cross-sectional study design with secondary data from the Integrated Hajj Computerized System for Health Sector (Siskohatkes) 2023. The population in this study was all elderly Hajj pilgrims recorded at Siskohatkes 2023 totaling 93,000 pilgrims. The sample used was 1,858 Hajj pilgrims aged ≥ 60 and hospitalized in Saudi Arabia. The data are analyzed at the multivariate level using the Cox Regression. Results: The study showed that the prevalence of pneumonia in elderly Indonesian Hajj pilgrims was 37.10% and the factor most significantly associated with the incidence of pneumonia was chronic obstructive pulmonary disease (COPD) comorbid (p-value <0.01; Adjusted PR= 1.43; 95%CI= 1.19–1.70). Conclusion: Comorbid COPD can increase the risk of elderly Hajj pilgrims being infected with pneumonia.